The Training Management Model to increase the capacity of Human Resources on the Santri Ready To (SSG) Daarut Tauhid Bandung - Indah Nurasiah (Pancaran Pendidikan, 2018)
View from the actuality of human resources is still considered low in Indonesia. Required efforts to meet the needs of the knowledge of the actual knowledge and skill of practical skills, especially that is immediately needed by the community. One of informal education institutions which organized the training in education and training institution Santri Ready To Daarut Monotheism is in Tawhid Daarut foundation in the way Gegerkalong Happy No 67. This research is a research on the management of the training is in the training institutions Santri Ready To (SSG) and is expected to provide information about the importance of the management of the program in an organization/community as one of the solution in the context of the efforts to increase the capacity of human resources. This research conducted in the headquarters of Command Santri Ready To Daarut Monotheism Bandung for 3 days since the date on 10-12 May 2016. The population in this research is the santri ready to performing tasks in the headquarters of command santri ready to numbered 10 respondents. The type of this research is a survey research without using the hypothesis. approach that is used in this research are mixed approach (mixed methods) that combines between qualitative and quantitative approach. Based on the above analysis it can be concluded that the great influence of Training Management variables together to increase the capacity of human resources is of 0,422 and then the remaining 0,578 determined by another variable. This information provides a description that the training Management variable provides a strong influence of knowledge to build the team. Thus it can be said that the management of the training has a significant impact on the knowledge to build the team.